POI01 Direct comparison of multiple nonlesional imaging measures to assess their power to measure treatment effects over 1 year in primary progressive multiple sclerosis. Issue 11 (22nd October 2010) - Arun, T; Smith, S; Weir, A P; Palace, J; Jenkinson, M
Abstract : Background: Improving the power of studies to detect neuroprotection is an urgent need in MS. The power of a parallel designed study will depend on the size of the measurement change and the variability of the measure across the patient group. We compared the use of different measures to assess their power in clinical trials in PPMS. Methods: 22 PPMS patients and seven healthy volunteers had brain and regional volumes, spinal cord area, corpus callosum (CC) and thalamic NAA concentrations, diffusion tensor (FA and MD) and magnetisation transfer outcomes calculated twice at baseline and twice at 1 year. Results: The mean/SD values using the average of the dual measures were greatest for grey matter volume (1.99), spinal cord area (1.93), whole brain volume (1.70), CC FA (1.49), CC NAA (1.39) and thalamic NAA (1.36), while being poor for all mean diffusivity measures (p≤0.89). On comparing MS patients and controls using two sample T-test, the greatest difference was seen in grey matter volume, CC FA, thalamic NAA, whole brain volume and whole brain magnetisation transfer (all p≤0.001). Conclusion: Although the gold standard imaging measure of neurodegeneration is presently whole brain volume change using registration methods other regional imaging measures may be more sensitive outcome measures in clinical trials. Their use singly or in combination should be explored.